Comparative analysis of right heart chamber remodeling after surgical and device secundum atrial septal defect closure in adults. (4th June 2018) - Foo, Jie Sheng; Lazu, Maksym; Pang, Si Ying; Lee, Phong Teck; Tan, Ju Le
Abstract : Background: To determine differences in right heart remodeling for patients with ASD who underwent surgical compared to device closure. Methods: Retrospective analysis of echo data of 121 adult patients with ASD from 2005 to 2015 performed prior to closure and within 6‐8 weeks, 6 months, and 1 year post closure. Results: 121 patients with median age of 39 were studied. Patients who underwent device closure were older (46 vs 37 years, P  < 0.05) with smaller mean ASD size (1.9 cm vs 2.3 cm, P  < 0.05). We observed a similar and significant reduction in right heart parameters and PASP for both surgical and device closure groups on serial echos up to 1 year. Device closure was associated with preservation of TAPSE compared to surgical closure (reduction of 0.2 cm vs 0.6 cm, P  < 0.001). Younger adults with ASD intervention (<40 years) had lower baseline PASP (33 mmHg vs 40 mmHg, P  < 0.05) compared to older adults (>40 years). This difference persisted up to 1 year with no difference in rate of right heart remodeling. The effects of device closure with better preservation of TAPSE and S' compared to surgery were consistent within both groups of younger and older adults. Conclusion: Device and surgical closure of ASD both result in similar improvements in right heart parameters. However, device closure is associated with better preservation of TAPSE at 1 year post intervention. Intervention for older adults with ASD, when compared to younger ones, did not result in a difference in rate of right heart remodeling.